The Role of Bhabinkamtibmas in Preventing Fraud During the Covid-19 Pandemic Period in the Legal Territory of Polewali Mandar Police - Abdau Wardiyoso (Police Studies Review, 2021)
The crime of fraud at Polewali Mandar Police has increased along with the spread of cases of Covid-19 which is caused by the corona virus. The implementation of social distancing and various kinds of restrictions have made Bhabinkamtibmas’ performance and strategy become less optimal than before. Based on data that has been collected, the writer choose to create a research which has a main purpose to determine an issue about role of Bhabinkamtibmas and factors that may influence and could prevent the fraud criminal at Polewali Mandar Subregional Police. This research is using a qualitative approach. A qualitative approach is the process of understanding a problem based on the informants' views in detail. This type of research is descriptive analytical, to provide a detailed description. The data sources of this research are using primary, secondary and tersier data sourced. The results of this study indicate that preventive activities carried out by Bhabinkamtibmas were already done but there are several factors that still become problems such as, it is not focused on delivering material about the crime of fraud, the large amount of area so that it becomes unreachable, awareness and information which are aimed to spread out to public couldn’t built maximally because most of people in Polewali Mandar are difficult to use Bahasa as main language. The advice which given regarding the problems above is optimizing the ayam com and whatsapp applications in Bhabinkamtibmas activities. Ayam com is a citizen journalism-based application that engages the public and Polri’s officer to inform each other about the conditions of peace and order in society such as distraction of peace & order in society or positive activities of Polri’s officer. Whatsapp application can be used by Bhabinkamtibmas in delivering peace and order in society messages for the target which is hard to reach or remote areas. Whatsapp is very efficient to use during the COVID-19 pandemic and further.